Much of the genetic risk of colorectal cancer is likely to be mediated through susceptibility to adenomas. - Carvajal-Carmona, L; Zauber, A; Jones, A; Howarth, K; Wang, J; Cheng, T; Riddell, R; Lanas, A; Morton, D; Bertagnolli, M; Tomlinson, I (2013)
Several single-nucleotide polymorphisms (SNPs) have been associated with colorectal cancer (CRC) susceptibility. Most CRCs arise from adenomas, and SNPs therefore might affect predisposition to CRC by increasing adenoma risk. We found that 8 of 18 known CRC-associated SNPs (rs10936599, rs6983267, rs10795668, rs3802842, rs4444235, rs1957636, rs4939827, and rs961253) were over-represented in CRC-free patients with adenomas, compared with controls. Ten other CRC-associated SNPs (rs6691170, rs6687758, rs16892766, rs7136702, rs11169552, rs4779584, rs9929218, rs10411210, rs4813802, and rs4925386) were not associated significantly with adenoma risk. Genetic susceptibility to CRC in the general population is likely to be mediated in part by predisposition to adenomas.